Integrating critical periods for bear cub survival into temporal regulations of human activities - Planella, Anna; Jiménez, José; Palomero, Guillermo; Ballesteros, Fernando; Blanco, Juan Carlos; López-Bao, José V. (Biological Conservation, 2019)
Conservation regulations are increasingly recognized as important elements of the available toolkit for effective biodiversity conservation. However, the full integration of evidence when designing these tools is still scarce, which limits the effectiveness of these legal instruments. Increasing concern is emerging on the compatibility between leisure activities and biodiversity conservation, which require a true integration of the best available evidence into policy-making. Managing authorities are required to take actions in order to ensure the compliance of international conservation commitments with species conservation. This is the case of applying spatio-temporal regulations on bear viewing activities in critical bear areas and periods, such as during the cub-rearing period. Here, we took advantage of a unique long-term dataset (>25 years) of observations of females with cubs in the endangered brown bear population in the Cantabrian Mountains, N Spain (>3000 observations from 329 females with cubs) to estimate monthly bear cub survival rates in the first sixteen months of cubs life. Overall, the monthly cub survival in this population was remarkable high, ranging from 0.839 to 0.994 monthly survival rates. The lower monthly cub survival rates were in May and June after the cubs left the den (mean ± SD: 0.839 ± 0.050 and 0.897 ± 0.023, respectively). Infanticide was estimated as the main mortality cause for cubs during the study period. Our results are practical because they can be used to inform conservation policies regarding the most appropriate periods to implement temporal regulations of human activities in bear breeding areas. The most appropriate period to implement such regulations here is the period between the time when the cubs leave the den (late March–April) until and including June; which should be considered in future temporal regulations adopted by Regional Governments in Spain. Accordingly, we also urge an update of the Spanish brown bear strategies considering the new scenario of ...